Chemometric challenges in development of paper-based analytical devices: Optimization and image processing - Hamedpour, Vahid; Oliveri, Paolo; Leardi, Riccardo; Citterio, Daniel (Analytica chimica acta, 2020)
Although microfluidic paper-based analytical devices (μPADs) get a lot of attention in the scientific literature, they rarely reach the level of commercialization. One possible reason for this is a lack of application of machine learning techniques supporting the design, optimization and fabrication of such devices. This work demonstrates the potential of two chemometric techniques including design of experiments (DoE) and digital image processing to support the production of μPADs. On the example of a simple colorimetric assay for isoniazid relying on the protonation equilibrium of methyl orange, the experimental conditions were optimized using a D-optimal design (DO) and the impact of multiple factors on the μPAD response was investigated. In addition, this work demonstrates the impact of automatic image processing on accelerating color value analysis and on minimizing errors caused by manual detection area selection. The employed algorithm is based on morphological recognition and allows the analysis of RGB (red, green, and blue) values in a repeatable way. In our belief, DoE and digital image processing methodologies are keys to overcome some of the remaining weaknesses in μPAD development to facilitate their future market entry. [Display omitted] •Optimization of device geometry and amount of assay reagent using D-optimal design.•Investigation of seven factors at three levels by only performing 44 trials.•MATLAB-based morphological recognition algorithm for signal readout.